A new consensus-based formation tracking scheme for a class of robotic systems using negative imaginary property. Issue 1 (2022) - Bhowmick, Parijat; Ganguly, Arijit; Sen, Sawan
Abstract: This brief proposes a consensus-based formation tracking scheme for multi-robot systems utilising the Negative Imaginary (NI) theory. The proposed scheme applies to a class of networked robotic systems that can be modelled as a group of single integrator agents with stable uncertainties connected via an undirected graph. NI/SNI property of networked agents facilitates the design of a distributed Strictly Negative Imaginary (SNI) controller to achieve the desired formation tracking. A new theoretical proof of asymptotic convergence of the formation tracking trajectories is derived based on the integral controllability of networked NI/SNI systems. The proposed scheme is an alternative to the conventional Lyapunov-based formation tracking schemes. It offers robustness to NI/SNI-type model uncertainties and fault-tolerance to a sudden loss of robots due to hardware/communication fault. The feasibility and usefulness of the proposed formation tracking scheme were validated by lab-based real-time hardware experiments involving miniature, two-wheeled mobile robots.